Global action for climate finance and investments for agrifood system transformation - Díaz-Bonilla, Eugenio; Echeverria, Ruben G.; Vos, Rob (T20 Indonesia, 2022)
The transformation of food systems is crucial for achieving multiple global objectives, including the 2030 Sustainable Development Goals (SDGs) and the climate change mitigation, adaptation and resilience goals established in the 2015 Paris Agreement. The Paris Agreement calls for “making finance flows consistent with a pathway towards low greenhouse gas emissions and climate-resilient development.” To meet national and global SDG-related and climate goals, existing flows of funds must be reoriented, and support mobilised for a broad range of investments and interventions, including mitigation and adaptation activities, by all food system actors. The brief proposes seven recommendations for the Group of 20 (G20) to act upon: (1) establish effective incentive frameworks to attract food-system finance; (2) improve regulatory frameworks to steer food consumption and production decisions towards sustainability and healthy diets; (3) encourage more strategic use of international development funds; (4) repurposing of existing agricultural support for the transformation of food systems; (5) promote climate-positive investment with funding from the commercial banking system and capital markets; (6) promote access of SMEs and smallholders to finance from commercial banking system and capital markets and (7) provide support to countries in aligning with the United Nations Forum on Sustainability Standards (UNFSS) National Pathways with the Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs) of the UN Framework Convention on Climate Change (UNFCCC)